Clinical and pathohistological characteristics of lupus nephritis in pediatric and adult population - Nikolic, Gorana; Mioljevic, Ana; Filipovic, Isidora; Radojevic Skodric, Sanja; Zivotic, Maja (Medical Research, 2023)
Introduction: Systemic lupus erythematosus (SLE) is an autoimmune disease, with abundant production of antibodies, deposits of immune complexes, and activation of the complement system, which disrupts the integrity and function of many organs, including the kidney. Although the frequency of SLE is less common in children, affected children develop lupus nephritis (LN) significantly more often, while in adults with SLE, LN occurs in 23% of cases, more often in males.Aim: The aim of this study was to analyze clinical parameters (gender, frequency of LN as the first manifestation of SLE, proteinuria, and serum creatinine values) and pathohistological parameters (frequency of LN classes, activity and chronicity index values, immunoglobulin deposit intensity and complement components at immunofluorescence, and blood vessels lesions) in the pediatric and adult populations of LN patients.Material and methods: The study included 218 biopsy samples of kidney tissue. Patients were divided into two groups: patients under 18 years of age (n=35) and those over 18 years of age (n =183).Results: Mean values of serum creatinine in pediatric population (71.6±16.4 µmol/l) were statistically significantly lower (p
Keywords: Systemic lupus erythematosus, Lupus nephritis, pediatric population, adult population.